Clinical Analysis on the Effects of Tandospirone Citrate Assisted by Drawing Therapy on Medication Compliance and Sleep Quality in Patients with Anxiety Disorders. (30th August 2022) - Hou, Jichong; Zhang, Ruifang
Abstract : Objective . To explore the clinical effects of tandospirone citrate assisted by drawing therapy (DT) on medication compliance and sleep quality in patients with anxiety disorders. Methods . A total of 128 patients with anxiety disorders treated in the hospital were enrolled between January 2020 and January 2022. According to the random number table method, they were divided into the observation group ( n  = 64) and the control group ( n  = 64). The control group was treated with tandospirone citrate, while the observation group was additionally treated with DT. The clinical curative effect and medication compliance after treatment, scores of Hamilton Anxiety Scale (HAMA), Pittsburgh Sleep Quality Index (PSQI), and the World Health Organization's Quality of Life Questionnaire-Brief Version (WHOQOL-BREF) before and after treatment were compared between the two groups. The occurrence of adverse reactions during treatment was recorded. Results . After treatment, the total response rate in the observation group was higher than that in the control group (96.88% vs 86.94%) (P < 0.05 ). After treatment, scores of HAMA and PSQI in both groups were decreased, which were lower in the observation group than in the control group (P < 0.05 ). After treatment, medication compliance in the observation group was higher than that in the control group (P < 0.05 ). After treatment, scores of environmental factors, social relations, physiological function, and psychological status in both groups were increased, which were higher in the observation group than in the control group (P < 0.05 ). During treatment, there was no significant difference in the incidence of adverse reactions between the two groups (P > 0.05 ). Conclusion . DT-assisted tandospirone citrate can effectively improve the clinical symptoms of patients with anxiety disorders, improve medication compliance, sleep quality, and quality of life, and have a certain degree of safety.